Implementation of al Maun Theology in Character Education in Muhammadiyah Schools - Ramadhani, Mudiana; Mustofa, Triono Ali (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Character education in Indonesia is currently facing serious challenges in the form of administrative formalities and a dichotomy between ritual piety and social reality. The phenomenon of bullying, corruption, and loss of empathy is clear evidence of moral deterioration. This research aims to explore the implementation of Al-Ma'un Theology as the foundation of character education in Muhammadiyah schools in overcoming the moral crisis. The research method used is qualitative with a literature study approach. The results of the study show that Al-Ma'un Theology transforms the understanding of religion from texts to social actions through three main pillars: the cultivation of the character of generosity, the internalization of social piety, and the use of the Ismuba curriculum as an instrument of value. This implementation succeeded in synergizing individual piety with public concern, where students were educated to have empathy for the poor through real philanthropic practices. In the digital era, Al-Ma'un values are relevant as a fortress of ethics and digital moral literacy. This research confirms that Al Ma'un-based character education creates 'organic intellectuals' who are not only personally pious, but also socially progressive, so as to be able to answer global humanitarian challenges and the nation's moral crisis.